Effects of six different microbial strains on polyphenol profiles, antioxidant activity, and bioaccessibility of blueberry pomace with solid-state fermentation - Tian, Zhu-Xi; Li, Yong-Fu; Long, Ming-Xiu; Liang, Qian; Chen, Xi; Huang, Dao-Mei; Ran, Yao-Qi (Frontiers in Nutrition, 2023)
To explore the effect of different microbial strains on blueberry pomace with solid-state fermentation (SSF), three fungi strains and three lactic acid bacteria (LAB) strains were utilized to investigate with respect to polyphenol profiles, antioxidant capacities, and bioaccessibility. Different strains exhibited different capacities for metabolizing polyphenolic compounds in blueberry pomace. The contents of 10 phenolic acids and 6 flavonoids (except (+)-catechin) were increased in blueberry pomace fermented by Lactobacillus acidophilus (LA). A similar tendency was observed in blueberry pomace fermented by Aspergillus niger (AN) and Lactobacillus plantarum (LP), where the concentration of 8 phenolic acids and 5 flavonoids was enhanced, with the following exceptions: (+)-catechin, ferulic acid, vanillic acid, and quercitrin. Chlorogenic acid and quercetin were the maximum phenolic acids and flavonoids in blueberry pomace with SSF, upgraded at 22.96 and 20.16%, respectively. Contrary to the growth of phenolic acids and flavonoid compounds, all individual anthocyanins showed a decreased trend. Only in the blueberry pomace fermented by AN, all anthocyanidins exhibit a rising trend. After SSF, 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS), 2,2-diphenylpicrylhydrazyl (DPPH), and ferric reducing antioxidant power (FRAP) radical scavenging abilities were increased by up to 33.56, 59.89, and 87.82%, respectively. Moreover, the simulated gastrointestinal digestion system revealed that SSF improved the bioaccessibility of polyphenolic compounds. Compared with other strains, LA, LP, and AN showed better excellent capacities for metabolizing polyphenolic compounds, which led to a greater increase in antioxidant activity and bioaccessibility in fermented blueberry pomace.